2000
DOI: 10.1046/j.1365-2257.2000.00272.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemolytic uraemic syndrome: prognostic factors

Abstract: Haemolytic uraemic syndrome (HUS) associated with Escherichia coli O157:H7 is the commonest cause of acute renal failure (ARF) in childhood. Production of verotoxin by the organism is pivotal in the pathogenesis of the disease. Verotoxin binds to a receptor on blood and endothelial cells, expressed as the P1 blood group antigen on red blood cells. A protective effect of the P1 phenotype has been proposed in this disease. This study investigates prognostic factors and the relationship between outcome and P1 phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…Taylor et al [5] and other studies [7][8][9][10] generated a hypothesis that expression of specific blood group antigens, such as ABO-B and P1, are protective against HUS. However, several more-recent analyses [7][8][9][10] have suggested that there is no association between P1 expression and infection outcome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Taylor et al [5] and other studies [7][8][9][10] generated a hypothesis that expression of specific blood group antigens, such as ABO-B and P1, are protective against HUS. However, several more-recent analyses [7][8][9][10] have suggested that there is no association between P1 expression and infection outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Taylor et al [5] and other studies [7][8][9][10] generated a hypothesis that expression of specific blood group antigens, such as ABO-B and P1, are protective against HUS. However, several more-recent analyses [7][8][9][10] have suggested that there is no association between P1 expression and infection outcome. The present study provides stronger data against a protective effect of P1, because it represents an analysis of children infected by a diversity of E. coli O157:H7 strains and not of children infected by a single strain, as in outbreaks [7,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, our fluid dynamic modeling reveals that the flow conditions in our system are comparable to those in the in vivo microvasculature. Finally, recent work characterizing blood flow in square and rectangular microchannels has shown that those geometries are suitable for blood rheology experiments (51).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our fluid dynamic modeling reveal that the flow conditions in our system are comparable to that in the in vivo microvasculature. Finally, recent work characterizing blood flow in square and rectangular microchannels has shown that those geometries are suitable for blood rheology experiments 15 .…”
Section: Figurementioning
confidence: 99%